Late Quaternary extinction of a tree species in eastern North America - Jackson, Stephen T. (National Academy of Sciences, 1999)
Widespread species- and genus-level extinctions of mammals in North America and Europe occurred during the last deglaciation [16,000–9,000 yr B.P. (by (14)C)], a period of rapid and often abrupt climatic and vegetational change. These extinctions are variously ascribed to environmental change and overkill by human hunters. By contrast, plant extinctions since the Middle Pleistocene are undocumented, suggesting that plant species have been able to respond to environmental changes of the past several glacial/interglacial cycles by migration. We provide evidence from morphological studies of fossil cones and anatomical studies of fossil needles that a now-extinct species of spruce (Picea critchfieldii sp. nov.) was widespread in eastern North America during the Last Glacial Maximum. P. critchfieldii was dominant in vegetation of the Lower Mississippi Valley, and extended at least as far east as western Georgia. P. critchfieldii disappeared during the last deglaciation, and its extinction is not directly attributable to human activities. Similarly widespread plant species may be at risk of extinction in the face of future climate change.